2020
DOI: 10.3389/fimmu.2020.01674
|View full text |Cite
|
Sign up to set email alerts
|

New MoDC-Targeting TNF Fusion Proteins Enhance Cyclic Di-GMP Vaccine Adjuvanticity in Middle-Aged and Aged Mice

Abstract: Cyclic dinucleotides (CDNs) are promising vaccine adjuvants inducing balanced, potent humoral, and cellular immune responses. How aging influences CDN efficacy is unclear. We examined the vaccine efficacy of 3 ′ ,5 ′-cyclic diguanylic acid (cyclic di-GMP, CDG), the founding member of CDNs, in 1-year-old (middle-aged) and 2-year-old (aged) C57BL/6J mice. We found that 1-and 2-year-old C57BL/6J mice are defective in CDG-induced memory T helper (Th)1 and Th17 responses and high-affinity serum immunoglobulin (Ig)G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The response to vaccine administration may decline with advancing age ( 135 , 136 ). Consequently, similar to many vaccines, the adjuvant potential of CDN vaccines is negatively affected by the aging process ( 137 ). Future animal research should explore the influence of mouse age on the efficacy of CDN vaccines and utilize mice that reflect the target age demographic, which may yield more precise experimental data for guiding clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…The response to vaccine administration may decline with advancing age ( 135 , 136 ). Consequently, similar to many vaccines, the adjuvant potential of CDN vaccines is negatively affected by the aging process ( 137 ). Future animal research should explore the influence of mouse age on the efficacy of CDN vaccines and utilize mice that reflect the target age demographic, which may yield more precise experimental data for guiding clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, Gogoi H et al reported that CDG (5 µg, i.n. )-induced high-affinity, durable antibodies, and Th1/Th17 responses were severely reduced in one-year-old (~equivalent age of 42.5-year-old in humans) and two-year-old (~equivalent age of 70-year-old in humans) C57BL/6J mice [95]. Aging decreases the response to vaccination [96][97][98][99].…”
Section: The Impact Of Age In Cdn Adjuvanticitymentioning
confidence: 98%
“…Similarly, immunization of an H1N1 influenza vaccine with cGAMP and saponin (Quil-A) significantly improved the survival (by 80–100%) of vaccinated 20-month-old mice, whereas cGAMP alone showed no significant improvement [ 143 ]. In this regard, recent studies found that targeting MoDCs with TNF fusion proteins restored the c-di-GMP adjuvantivity in aged mice [ 144 ].…”
Section: Cdns As Potent Vaccine Adjuvants For Systemic and Mucosal Immunizationmentioning
confidence: 99%